Adhesive films and flexible printed substrates

By stacking a high-temperature stable adhesive layer on the resin film layer of the flexible printed substrate, and using a high-oxygen permeability resin film layer and a high-temperature stable adhesive, the problem of peeling and cracking of the flexible printed substrate at high temperature is solved, and high heat resistance and stability are achieved.

CN112996227BActive Publication Date: 2025-03-25MEIKE TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202011393467.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-19
Filing Date
2020-12-02
Publication Date
2025-03-25
Estimated Expiration
2040-12-02

AI Technical Summary

Technical Problem

When the flexible printed substrate is placed at a high temperature exceeding 200°C for a long time, the oxidation of the conductor and thermal deterioration of the adhesive lead to the substrate peeling or cracking, which cannot meet the high-temperature application requirements of SiC and GaN power semiconductors.

Method used

An adhesive film with an adhesive layer laminated on the resin film layer is used. The adhesive layer contains a high-temperature stable adhesive, and its 3% thermal weight loss temperature is 320°C or more, and the oxygen permeability of the resin film layer at 200°C is less than 1.50×10-10cc·cm/cm2·sec·cmHg.

Benefits of technology

Significantly inhibits the oxidation deterioration of the conductor and the embrittlement of the adhesive, improves the heat resistance of the flexible printed substrate, and ensures that stability and circuit integrity can be maintained under high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112996227B_ABST
    Figure CN112996227B_ABST
Patent Text Reader

Abstract

An adhesive film and a flexible printed substrate having the adhesive film, wherein an adhesive layer is laminated on a resin film layer, the adhesive layer contains an adhesive, the adhesive layer is in a B-class state, and the oxygen permeability of the resin film layer at 200° C. measured according to JIS K7126-1 is 1.50×10 ‑10 cc cm / cm 2 ·sec·cmHg or less, and the 3% thermal weight loss temperature of the adhesive is 320°C or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an adhesive film and a flexible printed substrate. Background Art

[0002] Power devices are used in electronic devices for electric cars, automobiles, and airplanes. Since the Si semiconductor mounted on the power device will cause thermal runaway at temperatures above 150°C, heat dissipation devices such as cooling fans are required in conventional power devices.

[0003] However, SiC and GaN power semiconductors have emerged and are gaining attention because they are heat-resistant and can operate even at high temperatures of 225°C. Since power devices using SiC and GaN power semiconductors do not require cooling fans, power devices can be made smaller and lighter. Therefore, electronic substrates on which SiC and GaN semiconductors are mounted also require the same heat resistance at high temperatures of over 200°C as semiconductors.

[0004] As electronic substrates for mounting semiconductors, rigid substrates with glass cloth prepreg as cores or flexible printed circuit boards (hereinafter referred to as FPCs) that can be used for bending are used. Among them, the demand for the use of flexible printed circuit boards is increasing from the perspective of miniaturization and lightness of power devices.

[0005] The general structure of FPC includes: a support layer of a polyimide film having excellent heat resistance and insulation, a conductor such as copper foil formed on the support layer, a protective film, and an adhesive between the support layer and the protective film. As an adhesive for a flexible printed circuit board, an adhesive having a thermosetting resin such as epoxy resin as a main component is generally used (for example, Patent Document 1).

[0006] However, in order to apply the flexible printed circuit board to power devices using SiC and GaN power semiconductors, the flexible printed circuit board is required to have high heat resistance. From this point of view, Patent Document 2 discloses a metallized polyimide film with a small dimensional change rate when heated. In addition, Patent Document 3 also proposes a solution of using fluororubber (fluoro rubber) with excellent heat degradation resistance as a main component and mixing it with epoxy resin.

[0007] Prior art literature

[0008] Patent Literature

[0009] [Patent Document 1] Patent No. 3175338

[0010] [Patent Document 2] Japanese Patent Publication No. 2010-023380

[0011] [Patent Document 3] Patent No. 3555354 Summary of the invention

[0012] Technical problem to be solved by the invention

[0013] However, if the FPC is left at a high temperature of more than 200°C for a long time, the FPC will peel off or crack due to oxidation degradation of the conductor and thermal degradation of the adhesive. Here, oxidation degradation of the conductor means that oxides are generated due to oxidation of the conductor, and the oxides diffuse into the adhesive, or peeling occurs between the oxide layer and the layer without oxide generation, making the protective film easy to peel off.

[0014] In order to suppress the oxidation degradation of the conductor, it is proposed to use liquid crystal polymer (hereinafter referred to as LCP) for the protective film. However, it is found that LCP has a large thermal expansion coefficient, and there are problems such as substrate deformation and circuit disconnection due to long-term thermal degradation.

[0015] In addition, polyethylene naphthalate (hereinafter referred to as PEN) and the like have been proposed for use in pellicle membranes, but PEN has a problem in that it deforms due to heat.

[0016] Furthermore, among the adhesives used, epoxy adhesives generally used for flexible printed circuit boards have a problem of becoming brittle in a high temperature environment exceeding 200°C.

[0017] The present application solves the above-mentioned problems. That is, the present application provides an adhesive film and a flexible printed circuit board having excellent heat resistance.

[0018] Technical means to solve technical problems

[0019] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by using an adhesive film having the following constitution and a flexible printed circuit board using the adhesive film.

[0020] The adhesive film of the present application is an adhesive film in which an adhesive layer is laminated on a resin film layer.

[0021] The adhesive layer comprises an adhesive,

[0022] The bonding layer is in the B-grade state.

[0023] The oxygen permeability of the resin film layer at 200°C measured according to JIS K7126-1 is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less,

[0024] The 3% thermal weight loss temperature of the adhesive is 320° C. or higher.

[0025] In addition, the first flexible printed substrate of the present application has:

[0026] a laminated body having at least a first conductor formed with a circuit pattern, a support layer, and a second conductor formed with a circuit pattern in this order; and

[0027] The adhesive film of the present application,

[0028] The flexible printed circuit board is formed by contacting the adhesive layers of the adhesive film on both surfaces of the laminate.

[0029] In addition, the second flexible printed substrate of the present application has:

[0030] A laminated body comprising at least a support layer and a conductor having a circuit pattern formed thereon in this order; and

[0031] The adhesive film of the present application,

[0032] The flexible printed circuit board is formed by contacting the surface of the laminate having the conductor with the adhesive layer of the adhesive film.

[0033] The oxygen permeability of the support layer at 200°C is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less.

[0034] Effects of the Invention

[0035] According to the present application, an adhesive film and a flexible printed substrate having excellent heat resistance can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A schematic diagram showing an example of a first flexible printed substrate of the present application;

[0037] Figure 2 A schematic diagram showing an example of the second flexible printed circuit board of the present application.

[0038] Explanation of symbols:

[0039] 1: Support layer

[0040] 2: Conductor

[0041] 3: Laminated body

[0042] 4: Adhesive layer

[0043] 5: Resin film layer

[0044] 6: Adhesive film

[0045] 10, 20: Flexible printed circuit board DETAILED DESCRIPTION

[0046] In the present application, descriptions such as "XX or more and YY or less" and "XX to YY" indicating a numerical range mean a range including the lower limit and the upper limit as endpoints unless otherwise specified.

[0047] When a numerical range is described in sections, the upper limit and the lower limit of each numerical range can be arbitrarily combined.

[0048] The adhesive film of the present application is an adhesive film in which an adhesive layer is laminated on a resin film layer.

[0049] The adhesive layer comprises an adhesive,

[0050] The bonding layer is in the B-grade state.

[0051] The oxygen permeability of the resin film layer measured according to JIS K7126-1 at 200°C is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less,

[0052] The 3% thermal weight loss temperature of the adhesive is 320° C. or higher.

[0053] In addition, the first flexible printed substrate of the present application has:

[0054] a laminated body having at least a first conductor formed with a circuit pattern, a support layer, and a second conductor formed with a circuit pattern in this order; and

[0055] The adhesive film of the present application,

[0056] The flexible printed circuit board is formed by contacting the adhesive layers of the adhesive film on both surfaces of the laminate.

[0057] In addition, the second flexible printed substrate of the present application has:

[0058] A laminated body, the laminated body comprising at least a support layer and a conductor having a circuit pattern formed thereon in this order; and

[0059] The adhesive film of the present application,

[0060] The flexible printed circuit board is formed by contacting the surface of the laminate having the conductor with the adhesive layer of the adhesive film.

[0061] The oxygen permeability of the support layer at 200°C is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less.

[0062] In order to solve the above-mentioned problems, the present inventors first focused on the oxygen permeability of the resin film layer.

[0063] It has been found that polyimide, which has been used as a support layer or protective film of a flexible printed circuit board, generally has a high oxygen permeability. Therefore, it has been found that in a flexible printed circuit board using polyimide, oxygen in the air can pass through the polyimide or adhesive, and the oxygen reacts with the conductor to form oxides, causing oxidative degradation of the conductor. This phenomenon becomes significant in a high temperature environment exceeding 200°C.

[0064] Therefore, it is found that the resin films with low oxygen permeability under high temperature environment are used, specifically, the resin films with oxygen permeability of 1.50×10 -10 cc cm / cm 2 The resin film layer with a pressure of less than sec·cmHg can suppress the oxidative degradation of the conductor in a high temperature environment and prevent the peel strength of the protective film from decreasing.

[0065] The present inventors also focused on the 3% thermal weight loss temperature of the adhesive.

[0066] The present inventors have studied and found that conventional epoxy adhesives used for flexible printed circuit boards are thermally decomposed in a high temperature environment exceeding 200° C. to reduce their molecular weight, and this reduction in molecular weight causes the adhesive to become brittle.

[0067] Therefore, it was found that the use of an adhesive with high heat resistance, specifically, an adhesive with a 3% thermal weight loss temperature of more than 320°C, can suppress embrittlement caused by the low molecular weight of the adhesive even in a high temperature environment exceeding 200°C, and can also withstand use in power devices using SiC and GaN power semiconductors, providing a flexible printed substrate with excellent heat resistance.

[0068] Hereinafter, each material used in the present application will be described.

[0069] <Resin Film Layer>

[0070] The adhesive film has a resin film layer. The oxygen permeability of the resin film layer at 200° C. measured according to JIS K7126-1 is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less.

[0071] The oxygen permeability is preferably 1.00×10 -10 cc cm / cm 2 ·sec·cmHg or less, more preferably 1.00×10 - 11 cc cm / cm 2 ·sec·cmHg or less. The lower limit of the oxygen permeability is not particularly limited, but the lower the better. For example, it can be 1.00×10 -15 cc cm / cm 2·sec·cmHg or more.

[0072] The oxygen permeability can be controlled by the monomer components constituting the resin film. In addition, the oxygen permeability can also be controlled by coating an organic layer or an inorganic layer on the resin film, bonding an organic film or an inorganic film on the resin film, or adding an organic filler or an inorganic filler to the resin film.

[0073] The details of the method for measuring the oxygen permeability will be described below.

[0074] If the oxygen permeability of the resin film layer at 200°C is 1.50×10 -10 cc cm / cm 2 If the viscosity is less than ·sec·cmHg, there is no particular limitation and a known resin film can be used.

[0075] As the resin film layer, for example, a polyimide film, a liquid crystal polymer, etc. can be used. In addition, the resin film layer may include at least one selected from the group consisting of a polyimide film and a liquid crystal polymer.

[0076] The resin film layer may be composed of a single resin film or a laminated film of two or more resin films. In addition, a metal vapor-deposited film in which a metal such as aluminum is vapor-deposited on a resin film may also be used as the resin film layer.

[0077] As the resin film layer, specifically, UPILEX series (polyimide film produced by Ube Industries, Ltd.), Vexter series (liquid crystal polymer produced by Kuraray Co., Ltd.), etc. can be used.

[0078] When a Vexter series liquid crystal polymer is used as the resin film layer, Vexter CTF is preferred among the Vexter series from the viewpoint of oxygen permeability.

[0079] Moreover, when using a polyimide film as the resin film layer, it is preferable that the polyimide film contains polyimide which is a polymer of a tetracarboxylic acid component and a diamine component.

[0080] The tetracarboxylic acid component is not particularly limited, but is preferably at least one selected from the group consisting of biphenyltetracarboxylic acids such as 3,3',4,4'-biphenyltetracarboxylic acid, pyromellitic acid and their anhydrides, and esters of lower alcohols of these substances. The tetracarboxylic acid component more preferably contains 3,3',4,4'-biphenyltetracarboxylic acid, and further preferably contains 3,3',4,4'-biphenyltetracarboxylic acid dianhydride.

[0081] The diamine component is not particularly limited, but is preferably at least one selected from the group consisting of 1,4-phenylenediamine, 1,3-phenylenediamine, 1,2-phenylenediamine, 2,4-diaminotoluene, 2,5-diaminotoluene, and 2,6-diaminotoluene.

[0082] The polyimide film preferably comprises a polyimide as a polymer, the polymer being a polymer comprising at least one monomer selected from the group consisting of 1,2-phenylenediamine, 1,3-phenylenediamine, 1,4-phenylenediamine, and 3,3′,4,4′-biphenyltetracarboxylic acid dianhydride. More preferably, the polyimide film comprises a polyimide as a polymer, the polymer being a polymer comprising at least 1,4-phenylenediamine and 3,3′,4,4′-biphenyltetracarboxylic acid dianhydride.

[0083] If the polyimide film includes the above-mentioned polyimide, since unit structures of the polyimide overlap with each other to form a structure through which oxygen is more difficult to pass, it is preferable.

[0084] Specific examples of the polyimide film corresponding to the polymer containing monomers of at least 1,4-phenylenediamine and 3,3′,4,4′-biphenyltetracarboxylic dianhydride include UPILEX-S and the like.

[0085] <Adhesive>

[0086] The adhesive film has an adhesive layer laminated on the resin film layer. The adhesive layer contains an adhesive. The adhesive has a 3% thermal weight loss temperature of 320° C. or higher.

[0087] The 3% thermal weight loss temperature of the binder is preferably 350° C. or higher, more preferably 370° C. or higher. Although the upper limit of the 3% thermal weight loss temperature is not particularly limited, it is preferably 600° C. or lower from the viewpoint of laser processability.

[0088] The 3% thermal weight loss temperature can be controlled by optimizing the molecular structure, optimizing the cross-linking density, and the like.

[0089] If the 3% weight loss temperature is above 320°C, the adhesive is not limited and a known adhesive can be used. For example, the adhesive can be an acrylic rubber adhesive or an epoxy resin adhesive. In addition, an adhesive containing fluororubber can also be used. Among them, from the viewpoint of heat resistance, an adhesive containing fluororubber is preferred. The fluororubber may have an unsaturated bond or may not have an unsaturated bond, but it is more preferred to have an unsaturated bond.

[0090] Fluororubber having unsaturated bonds can be obtained by introducing unsaturated bonds into fluororubber by a known method, for example, alkaline modification (salt modification) such as alkali modification can be used.

[0091] The present inventors speculate as follows as to why the heat resistance is improved when the adhesive contains fluororubber:

[0092] It is known that the bond energy between carbon and fluorine (between CF) is greater than the bond energy between carbon and hydrogen (between CH). Therefore, by modifying the rubber with fluorine to increase the CF bond, the breakage of the bond between the elements caused by heat can be prevented. In addition, if the bond between carbon and carbon (between CC) in the main chain of the resin is easy to rotate, the case of fluorine modification (i.e., the case of -CF2-) is more difficult to rotate compared to the case without fluorine modification (i.e., the case of -CH2-), and the bond energy is improved. Therefore, thermal decomposition becomes difficult to occur, and heat resistance is improved.

[0093] Furthermore, when the fluororubber has an unsaturated bond, the unsaturated bond can react with the thermosetting resin described below, thereby improving heat resistance.

[0094] As the fluororubber, there can be mentioned a polymer or copolymer of at least one monomer selected from the group consisting of vinyl fluoride, vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene, etc. More preferably, it is a copolymer of at least one monomer selected from the group consisting of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene, etc. The copolymer is preferably a binary copolymer or a ternary copolymer, and more preferably a binary copolymer.

[0095] Examples of the fluororubber having an unsaturated bond include those in which the above-mentioned polymers or copolymers have been introduced with an unsaturated bond.

[0096] In the copolymer, fluorinated olefins such as ethylene, propylene, alkyl vinyl ether, hexafluoroisobutylene, vinyl acetate, and the like, olefins, vinyl compounds, and the like may be copolymerized to the extent that the effects of the present application are not impaired.

[0097] Specifically, for example, polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, a vinylidene fluoride-hexafluoropropylene copolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, a chlorofluoroethylene-vinylidene fluoride copolymer, and unsaturated bond-introduced products thereof are exemplified.

[0098] Preferred are vinylidene fluoride-hexafluoropropylene copolymers and unsaturated bond-introduced products of the copolymers, and more preferred are unsaturated bond-introduced products of vinylidene fluoride-hexafluoropropylene copolymers. The copolymerization ratio (vinylidene fluoride:hexafluoropropylene) is preferably 3:7 to 9.5:0.5, preferably 5:5 to 9:1, based on mass.

[0099] The fluororubber may be used alone or in combination of two or more. Furthermore, a fluororubber having no unsaturated bond and a fluororubber having an unsaturated bond may be used simultaneously.

[0100] Mooney viscosity (ML) of fluororubber or fluororubber with unsaturated bonds 1+10 (121°C) is preferably 40 to 110. If it is within the above range, the sheet processability is excellent, and the elastic modulus and elongation coefficient are within the appropriate range. Therefore, the mold release processability, adhesion at high temperature, welding heat resistance, adhesion after high temperature and long-term durability test, and processability in the B-level state will become good. Mooney viscosity (ML 1+10 (121°C)) is more preferably 50 to 100.

[0101] The Mooney viscosity can be controlled by, among other things, the molecular weight of the material. For example, the Mooney viscosity can be made greater by increasing the molecular weight.

[0102] The Mooney viscosity was measured according to JIS K 6300-1 (2013). The viscosity was measured using a Mooney viscometer SMV-201 (manufactured by Shimadzu Corporation) under the conditions of a temperature of 121° C., a preheating time of 1 minute, and a rotor rotation time of 10 minutes.

[0103] For these polymers or copolymers, if necessary, they can be treated with alkaline substances such as potassium hydroxide, sodium hydroxide, cesium hydroxide, calcium hydroxide, calcium carbonate, triethylamine, etc. in the presence of ketone solvents such as acetone and methyl ethyl ketone, preferably at a temperature of about 20 to 70° C., and the unsaturated bonds can be formed in the molecules through the reaction of removing hydrogen fluoride.

[0104] The unsaturated bond content (-CH=CH- content) in the fluororubber having an unsaturated bond is preferably 0.1 to 30% by mass, more preferably 0.5 to 10% by mass. Commercially available fluororubbers and fluororubbers having an unsaturated bond may also be used.

[0105] Examples of the acrylic rubber include polymers of vinyl monomers containing an alkyl (meth)acrylate as a main component.

[0106] Examples of the alkyl (meth)acrylate include monomers such as ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate; monomers having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and allyl alcohol; and monomers having an epoxy group of an epichlorohydrin-modified product such as glycidyl (meth)acrylate and dimethylaminoethyl (meth)acrylate. The alkyl (meth)acrylate may be used alone or in combination of two or more.

[0107] Examples of vinyl monomers other than alkyl (meth)acrylates include, but are not limited to, monomers having a carboxyl group such as acrylic acid and methacrylic acid, acrylonitrile, and styrene. Vinyl monomers other than alkyl (meth)acrylates may be used alone or in combination of two or more.

[0108] The acrylic rubber may be copolymerized with a monomer other than a vinyl monomer. That is, the acrylic rubber may be a copolymer of a vinyl monomer and a monomer other than a vinyl monomer. Examples of monomers other than a vinyl monomer include, but are not limited to, monomers having a carboxyl group, such as itaconic acid, crotonic acid, maleic acid, and maleic anhydride. Monomers other than a vinyl monomer may be used alone or in combination of two or more.

[0109] Generally speaking, the saturated bonds in the main chain of acrylic rubber have high thermal stability, and have heat resistance and oil resistance second only to fluororubber, and are used in automobile applications, etc. In addition, if acrylonitrile is used as a monomer that becomes a raw material of acrylic rubber, the nitrile group promotes polarization between CCs in the main chain, further improving the bonding force, and therefore it is preferred.

[0110] As the acrylic rubber, it is preferred to use an acrylic rubber synthesized by suspension polymerization. Since the suspension polymerization does not require a salting-out process, the acrylic rubber synthesized by the suspension polymerization is hardly affected by the emulsifier that causes migration reduction. As the acrylic rubber synthesized by the suspension polymerization, an acrylic rubber produced by a known method or a commercially available acrylic rubber can be used without particular limitation. As commercially available acrylic rubber, for example, TEISANRESIN SG 708-6 produced by Nagase ChemteX Co., Ltd. can be cited.

[0111] <Thermosetting resin>

[0112] The adhesive may also be an adhesive composition. The adhesive composition may contain a thermosetting resin.

[0113] Thermosetting resins preferably have a softening point of 30°C or higher. In other words, they are preferably solid at room temperature (25°C). The softening point is more preferably 30°C to 160°C, further preferably 40°C to 160°C, further more preferably 50°C to 150°C, and particularly preferably 60°C to 130°C.

[0114] In the manufacturing process of printed wiring boards such as flexible printed circuit boards, it is sometimes necessary to perform processing such as opening holes for component mounting in the B-stage (semi-cured) state before hot pressing. By using a thermosetting resin that is solid at room temperature and has a softening point in the above range, the miscibility with acrylic rubber and fluororubber becomes good, and combined with the elastic modulus improvement effect of the inorganic filler described later, the processability in the B-stage state becomes better.

[0115] The softening point of the resin can be measured by the ring and ball method of JIS K 7234. As the measuring device, for example, a METTLER softening point measuring device (FP 900 calorific value analysis system) manufactured by METTLER TOLEDO can be used.

[0116] From the viewpoint of reactivity and heat resistance, the thermosetting resin is preferably any one of a phenolic resin and an epoxy resin, or a mixture of two or more thereof.

[0117] Examples of epoxy resins include bisphenol-type epoxy resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin; novolac-type epoxy resins such as phenol novolac-type epoxy resin, cresol novolac-type epoxy resin, and bisphenol A novolac-type epoxy resin; alicyclic epoxy resins; chain aliphatic epoxy resins; diglycidyl ethers of bisphenols; diglycidyl ethers of naphthalene diols; diglycidyl ethers of phenols; diglycidyl ethers of alcohols; and alkyl-substituted products and hydrogenated products thereof. One epoxy resin may be used alone, or two or more epoxy resins may be used in combination.

[0118] Phenolic resin is the product of an addition reaction between phenols and aldehydes using acid or base as a catalyst.

[0119] Examples of the phenols include phenol, m-cresol, p-cresol, o-cresol, isopropylphenol, and nonylphenol.

[0120] As aldehydes, formaldehyde, paraformaldehyde, acetaldehyde, paraldehyde, butyraldehyde, octanal, benzaldehyde, etc. can be listed. Generally, formaldehyde and paraformaldehyde are used. In addition, vegetable oil-modified phenolic resin can also be used. Vegetable oil-modified phenolic resin is obtained by reacting phenols with vegetable oils in the presence of an acid catalyst, and then reacting aldehydes in the presence of a base catalyst. As acid catalysts, p-toluenesulfonic acid, etc. can be listed. As base catalysts, amine catalysts such as ammonia, trimethylamine, and triethylamine can be listed.

[0121] In addition, as the thermosetting resin, xylene resin, guanamine resin, diallyl phthalate resin, vinyl ester resin, unsaturated polyester resin, furan resin, polyimide resin, polyurethane resin, cyanate resin, maleimide resin, benzocyclobutene resin, etc. can be used.

[0122] The thermosetting resin preferably includes an epoxy resin, and preferably an epoxy resin. The epoxy resin is preferably a cresol novolac epoxy resin, and more preferably an o-cresol novolac epoxy resin. Such epoxy resins can use commercial products, and for example, YDCN 700-10 (Nippon Steel & Sumitomo Metal Chemical Co., Ltd.), N695 (DIC Corporation) and the like can be cited.

[0123] The content of the thermosetting resin is preferably 8 to 120 parts by mass relative to 100 parts by mass of the fluororubber. Within the above range, mold release processability and adhesion at high temperatures become good. The content is more preferably 8 to 110 parts by mass, and further preferably 8 to 100 parts by mass.

[0124] When the adhesive is an acrylic rubber adhesive, the acrylic rubber is preferably used in combination with a thermosetting resin. As the thermosetting resin, from the aspect of reactivity and heat resistance, epoxy resin, phenolic resin and their mixtures are preferred. In addition, although there is no particular restriction on the weight average molecular weight, softening point, etc. of the epoxy resin and phenolic resin, the above-mentioned epoxy resin and phenolic resin can be preferably used.

[0125] The content of the thermosetting resin used in combination with the acrylic rubber is preferably 10 to 200 parts by mass, more preferably 15 to 150 parts by mass, and particularly preferably 20 to 120 parts by mass, relative to 100 parts by mass of the acrylic rubber. If it is 10 parts by mass or more, the heat resistance will be higher. In addition, if it is 200 parts by mass or less, the adhesion will be higher.

[0126] <Inorganic filler>

[0127] The adhesive composition may contain an inorganic filler. A known inorganic filler may be used. The inorganic filler is preferably an electrically insulating material.

[0128] Examples thereof include silicon dioxide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, calcium silicate, aluminum silicate, calcium carbonate, aluminum oxide, magnesium oxide, antimony oxide, tin oxide, titanium oxide, manganese oxide, zirconium oxide, silicon nitride, aluminum nitride, boron nitride, talc, mica, and kaolin.

[0129] Since acrylic rubber and fluororubber have low elastic modulus, adhesive burrs may be generated and adhesive may adhere to the processed portion when processed in the B-stage state. In contrast, the use of an inorganic filler in the adhesive composition can increase the elastic modulus and improve processability.

[0130] The inorganic filler is preferably a material with thixotropic properties that condenses to a certain extent and easily increases the elastic modulus. From this point of view, silicon dioxide, aluminum hydroxide, talc, etc. are preferred, and silicon dioxide is more preferred. Silica can be used without restriction in the form of dry silicon dioxide or wet silicon dioxide. Commercially available silicon dioxide can also be used. For example, AEROSIL200 (Japan Aerosil Co., Ltd.) can be cited.

[0131] The inorganic filler may be subjected to a hydrophobic treatment. Examples of the hydrophobic treatment include silicone oil treatment and silane coupling agent treatment.

[0132] The number average particle size of the primary particles of the inorganic filler is preferably about 10 nm to 100,000 nm, more preferably about 50 nm to 10,000 nm.

[0133] The content of the inorganic filler is preferably 1 to 35 parts by mass, more preferably 1 to 30 parts by mass, and further preferably 3 to 25 parts by mass, relative to 100 parts by mass of the fluororubber. Within the above range, in addition to processability, adhesion, welding heat resistance, and high-temperature and long-term durability become good.

[0134] <Amine compounds>

[0135] The adhesive composition may further include an amine compound as a curing agent.

[0136] As a curing agent for the thermosetting resin such as epoxy resin, dicyandiamide is preferably used, which has a low curing initiation temperature and excellent stability at room temperature. If necessary, an imidazole compound may be used as a curing aid.

[0137] Furthermore, as a curing agent for fluororubber having an unsaturated bond, the amine compound is preferably an aromatic diamine compound from the viewpoint of curability.

[0138] Examples of the aromatic diamine compound include compounds represented by the following structural formula (I).

[0139] [Chemistry 1]

[0140]

[0141] [In formula (I), R 1 , R 2 are each independently an alkyl group having 1 to 6 carbon atoms, R 3 It is at least one selected from the group consisting of an alkylene group having 1 to 6 carbon atoms, an aromatic hydrocarbon group, a carbonyl group, a fluorenyl group, a sulfonyl group, an ether group, and a thioether group, and m and n are integers of 0 to 4, respectively.]

[0142] Preferred examples of the alkyl group include a methyl group, an ethyl group, and a propyl group. From the viewpoint of curability, the alkyl group is more preferably a methyl group or an ethyl group.

[0143] Preferred examples of the alkylene group include a methylene group and an ethylene group. From the viewpoint of curability, the alkylene group is more preferably a methylene group.

[0144] From the viewpoint of storage stability and rapid curing properties, m and n are each independently preferably an integer of 0 to 2, more preferably 1 or 2, and even more preferably 2.

[0145] In the formula, from the viewpoint of curability, the configuration of -NH2 is preferably relative to R 3 The counterpoint.

[0146] The aromatic hydrocarbon group is not particularly limited as long as it is divalent. Examples thereof include phenylene. The aromatic hydrocarbon group may have a substituent such as a methyl group.

[0147] R 3 It may be a substituent formed by combining an aromatic hydrocarbon group and an alkylene group, and there is no particular limitation on the combination of the aromatic hydrocarbon group and the alkylene group. For example, an alkylene group having an aromatic hydrocarbon group may be mentioned. Specifically, for example, two alkylene groups are bonded via an aromatic hydrocarbon group, an aromatic hydrocarbon group is bonded as a side chain of an alkylene group, an aromatic hydrocarbon group is bonded to an alkylene group, and an aromatic hydrocarbon group and an alkylene group are bonded to two benzene rings shown in formula (I) respectively. Examples of the aromatic hydrocarbon group include benzene rings and naphthalene. The aromatic hydrocarbon group may have a substituent such as a methyl group.

[0148] Among the compounds shown in formula (I), 4,4′-methylenebis(2-ethyl-6-methylaniline) is particularly preferred.

[0149] The content of the amine compound is preferably 0.1 to 20 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the fluororubber. It is also preferred that the content of the amine compound is 0.5 to 30 parts by mass relative to 100 parts by mass of the epoxy resin.

[0150] <Adhesive Composition>

[0151] The adhesive composition can be obtained by mixing acrylic rubber or fluororubber with other additives such as thermosetting resin, inorganic filler, curing agent, etc. as required. During the mixing, an organic solvent can also be used as required.

[0152] Preferably, the adhesive or adhesive composition is used to manufacture a flexible printed substrate.

[0153] For example, an adhesive film using an adhesive or an adhesive composition can also be obtained and used for production of a flexible printed substrate.

[0154] The elastic modulus of the adhesive layer measured according to the test method for tensile properties of JIS K 7127 (or the elastic modulus of the adhesive composition in the B-stage state (semi-cured state)) is preferably above 15 MPa, more preferably above 20 MPa. There is no particular restriction on the upper limit, but it is preferably below 3000 MPa, more preferably below 1000 MPa, and further preferably below 100 MPa.

[0155] In addition, the elongation at break of the adhesive layer measured according to the test method of JIS K 7127 (1999) tensile properties (or the elongation at break of the adhesive composition when it is in the B-stage state (semi-cured state)) is preferably less than 400%, more preferably less than 300%, and further preferably less than 200%. There is no particular restriction on the lower limit, but it is preferably more than 50%, more preferably more than 100%.

[0156] When the elastic modulus and the elongation at break are within the above ranges, the processability becomes good. The elastic modulus and the elongation at break can be controlled by the softening point of the thermosetting resin, the Mooney viscosity of the fluororubber, the content of the inorganic filler, and the like.

[0157] The adhesive film can be manufactured by a known method. For example, an organic solvent solution of the above-mentioned adhesive composition is prepared and applied on a resin film layer such as a polyimide to form an adhesive layer. Then, for example, it is dried under the conditions of 50°C to 160°C for 1 minute to 15 minutes to make the adhesive layer a B-grade state to obtain an adhesive film. Thereafter, the obtained adhesive film can be attached to an adherend and thermally cured.

[0158] In the manufacture of a flexible printed circuit board, when the above-mentioned adhesive composition is used for bonding a protective film or a carrier film, bonding is also performed in the same manner, thereby obtaining a flexible printed circuit board having an adhesive layer containing a cured product of the adhesive composition. During the period from the B-stage state to the heat curing, hole opening processing, etc. may also be performed as needed.

[0159] The method for obtaining the B-stage adhesive composition is not particularly limited, and a known method including the above-mentioned heating and drying method can be used.

[0160] There is no particular limitation on the organic solvent, and known organic solvents can be used. Examples thereof include acetone, methyl ethyl ketone, tetrahydrofuran, chloroform, dimethylformamide, methyl isobutyl ketone, and the like. There is no particular limitation on the amount of the organic solvent used, but it is preferably used in a range of 10% to 70% by mass, more preferably 20% to 40% by mass, so that the solid content is contained.

[0161] <Flexible Printed Circuit Board>

[0162] The first flexible printed substrate of the present application has:

[0163] a laminated body having at least a first conductor formed with a circuit pattern, a support layer, and a second conductor formed with a circuit pattern in this order; and

[0164] The adhesive film of the present application,

[0165] The flexible printed circuit board is formed by contacting the adhesive layers of the adhesive film on both surfaces of the laminate.

[0166] Figure 1 A schematic diagram showing an example of the first flexible printed substrate of the present application. Figure 1 In the embodiment, the conductor 2 is attached to both sides of the support layer 1 to form a laminate 3 (in Figure 1 In the embodiment, the first conductor and the second conductor are collectively referred to as “conductors”.) Furthermore, the adhesive film 6 of the adhesive layer 4 laminated on the resin film layer 5 is in contact with the adhesive layer 4 on both sides of the laminate 3.

[0167] By adopting such a structure, it is possible to prevent oxygen from penetrating into the flexible printed substrate from both surfaces of the flexible printed substrate.

[0168] As the first conductor and the second conductor, known materials can be used without particular limitation. Examples thereof include copper, silver, gold, tin, aluminum, indium, and alloys of these metals. Preferably, the conductor is a copper-containing material, more preferably copper foil. The material of the first conductor and the material of the second conductor may be the same or different.

[0169] The thickness of the first conductor and the thickness of the second conductor are not particularly limited, but are preferably 5 to 70 μm, more preferably 12.5 to 50 μm. The thickness of the first conductor and the thickness of the second conductor may be the same or different.

[0170] There is no particular limitation on the support layer, and for example, polyimide, polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide and other super engineering plastics can be used. Preferably, the support layer is polyimide.

[0171] The thickness of the support layer is not particularly limited, but is preferably 5 to 50 μm, more preferably 12.5 to 30 μm. It is preferred to appropriately select the thickness of the support layer depending on the intended use.

[0172] In addition, if the oxygen permeability of the support layer at 200°C is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less (preferably 1.00×10 -10 cc cm / cm 2 ·sec·cmHg or less, more preferably 1.00×10 -11cc cm / cm 2 ·sec·cmHg or less. For example, at 1.00×10 -15 cc cm / cm 2 ·sec·cmHg or more), the following second flexible printed circuit board may also be used.

[0173] That is, the second flexible printed substrate of the present application has:

[0174] A laminated body, the laminated body comprising at least a support layer and a conductor having a circuit pattern formed thereon in this order; and

[0175] The adhesive film of the present application,

[0176] The flexible printed circuit board is formed by contacting the surface of the laminate having the conductor with the adhesive layer of the adhesive film.

[0177] The oxygen permeability of the support layer at 200°C is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less.

[0178] Figure 2 A schematic diagram showing an example of a second flexible printed substrate of the present application. Figure 2 In the embodiment, the conductor 2 is attached to one surface of the support layer 1 to form a laminate 3. In addition, the adhesive layer 4 of the adhesive film 6 of the adhesive layer 4 laminated on the resin film layer 5 is in contact with the surface of the laminate 3 having the conductor 2.

[0179] With such a structure, since the oxygen permeability of the support layer at 200° C. is low, even if the surface of the laminate 3 without the conductor 2 is not in contact with the adhesive film of the present application, oxygen can be prevented from penetrating into the flexible printed circuit board.

[0180] The conductor on the second flexible printed circuit board of the present application may be the same conductor as the first conductor and the second conductor on the first flexible printed circuit board.

[0181] In addition, if the oxygen permeability of the support layer on the second flexible printed substrate of the present application at 200°C is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less, there is no particular limitation, and for example, the same material as the resin film layer on the adhesive film of the present application can be used.

[0182] Example

[0183] Hereinafter, the present application will be described in detail with reference to the examples. However, the present application is not limited to the following examples. In addition, in the following formulations, unless otherwise specified, "parts" are based on mass.

[0184] The oxygen permeability was measured using a polyimide film UPILEX-S (thickness 25 μm) produced by Ube Industries, Ltd. as the resin film. In addition, the appearance after the heat resistance test was observed. The conditions are as follows. In addition, the results are shown in Table 1.

[0185] (Determination of oxygen permeability)

[0186] Measurement method: JIS K7126-1, according to Annex 2

[0187] Test gas type: oxygen

[0188] Test gas flow rate: 90ml / min

[0189] Carrier gas type: Helium

[0190] Carrier gas flow rate: 35ml / min

[0191] Transmission area: 15.2cm 2

[0192] Measuring device: GTR-10AH (200°C) or GTR-30XANO (~120°C), both manufactured by GTR TEC

[0193] Thermostatic bath temperature: 25℃, 120℃, 200℃

[0194] Gas chromatography detection method: 2 detection volumes of 0.0μl and 15.3μl (heat resistance test)

[0195] The resin film of 100 mm square was heated for 500 hours in an oven at 200° C. or 250° C. under atmospheric conditions. The appearance of the resin film after heating was evaluated according to the following criteria.

[0196] <Evaluation Criteria>

[0197] A: The warping of all edges of the 100 mm square evaluation piece was less than 10 mm.

[0198] B: The warpage at one or more edges of the 100 mm square evaluation piece is 10 mm or more and less than 30 mm.

[0199] C: The warping of one or more locations on the edge of the 100 mm square evaluation piece is 30 mm or more.

[0200] The oxygen permeability of each resin film and the appearance after the heat resistance test were measured in the same manner except that the resin film was changed to the following one.

[0201] KAPTON EN-S: KAPTON EN-S polyimide film produced by Toray DuPont (thickness 25μm)

[0202] LCP-CTF: Liquid crystal polymer Vester CTF produced by Kuraray Co., Ltd. (thickness 50μm)

[0203] LCP-CTQ: Liquid crystal polymer Vexter CTQ produced by Kuraray Co., Ltd. (thickness 25μm)

[0204] PEN: Teonex Q51 manufactured by Teijin Limited (thickness 25 μm)

[0205] PET: Lumirror 25S (thickness 25 μm) manufactured by Toray Industries, Inc.

[0206] Al / PET: Aluminum-deposited PET Teto-Light (thickness 12 μm) produced by Oike Advanced Film Co., Ltd.

[0207] Table 1

[0208]

[0209] In Table 1, the term “E-xx” means “×10 -xx In addition, the unit of oxygen permeability is cc·cm / cm 2 ·sec·cmHg.

[0210] Example 1

[0211] Acrylic rubber (A)

[0212] Acrylic rubber (SG 708-6 manufactured by Nagase ChemteX Co., Ltd.) 80 parts

[0213] · Epoxy resin (solid, softening point 95°C) o-cresol novolac type epoxy resin (N695 (DIC Corporation) 20 parts

[0214] Silica (fumed silica: AEROSIL 200 (Japan Aerosil Co., Ltd.) 15 parts

[0215] Curing agent: 0.2 parts of dicyandiamide

[0216] The solid content was dissolved in methyl ethyl ketone to 30% by mass to obtain a pressure-sensitive adhesive composition containing acrylic rubber. The 3% thermal weight loss temperature of the obtained pressure-sensitive adhesive composition was 330° C. Silica was dispersed using a bead mill.

[0217] In addition, the solution of the obtained adhesive composition is coated on a polyimide film (UPILEX-S polyimide film produced by Ube Industries, Ltd., with a thickness of 25 μm) so that the thickness after drying is 25 μm, and dried with a hot air dryer at 140°C for 3 minutes to obtain an adhesive film in a B-stage state (semi-cured state).

[0218] The adhesive coated surface of the adhesive film was heat-pressed to the black treated surface of copper foil (BHY, 18 μm thick, produced by JX Nippon Mining & Metallurgy Co., Ltd.) using a vacuum laminator at 160°C, 3 MPa, and reduced pressure for 30 seconds. Then, the film was heat-cured at 160°C for 10 hours to obtain the test sample of Example 1. The following evaluation was performed using the obtained test sample. The results are shown in Table 2.

[0219] Example 2

[0220] · Fluorine rubber double bond modification (unsaturated modified product of binary copolymer of vinylidene fluoride and hexafluoropropylene (copolymer ratio: vinylidene fluoride / hexafluoropropylene = 8 / 2), Mooney viscosity (ML 1+10 (121°C)): 98, double bond content: 4 mass %) 100 parts

[0221] Silica (fumed silica: AEROSIL 200 (Japan Aerosil Co., Ltd.) 15 parts

[0222] · Epoxy resin (solid, softening point 95°C) o-cresol novolac type epoxy resin (N695 (DIC Corporation) 20 parts

[0223] · Amine compound (4,4′-methylenebis(2-ethyl-6-methylaniline): Curehard MED-J produced by Kumiai Chemical Industries, Ltd.) 5 parts

[0224] The solid content was dissolved in methyl ethyl ketone to 30% by mass to obtain an adhesive composition containing fluororubber. The 3% thermal weight loss temperature of the obtained adhesive composition was 373° C. Silica was dispersed using a bead mill.

[0225] In addition, the solution of the obtained adhesive composition was coated on a polyimide film (Ube Industries, Ltd. polyimide film UPILEX-S, thickness 25 μm) so that the thickness after drying was 25 μm, and dried with a hot air dryer at 140°C for 3 minutes to obtain an adhesive film in a B-stage state (semi-cured state).

[0226] The adhesive coated surface of the adhesive film was heat-pressed to the black treated surface of copper foil (BHY, 18 μm thick, produced by JX Nippon Mining & Metallurgy Co., Ltd.) using a vacuum laminator at 160°C, 3 MPa, and reduced pressure for 30 seconds. Then, the film was heat-cured at 160°C for 10 hours to obtain the test sample of Example 2. The following evaluations were performed using the obtained test sample. The results are shown in Table 2.

[0227] (Peel strength (23°C))

[0228] The peel strength of the test sample of Example 1 or Example 2 was measured by peeling the resin film in a 90° direction at a speed of 50 mm / min in an atmosphere of 23°C using a tensile tester (Shimadzu Autograph).

[0229] In addition, the peel strength of the test sample of Example 1 or Example 2 was measured in the same manner after the test sample was heated in an oven at 200° C. or 250° C. for 500 hours or 1000 hours under atmospheric conditions.

[0230] A larger peel strength value indicates better heat resistance.

[0231] (Heat resistance test)

[0232] The test sample of Example 1 or Example 2 and the test sample were heated in an oven at 200° C. or 250° C. for 500 hours or 1000 hours under atmospheric conditions. The appearance of each test sample after heating was evaluated according to the following criteria.

[0233] <Evaluation Criteria>

[0234] A: There was no peeling between the adhesive film and the copper foil, and the adhesive was not brittle.

[0235] B: The adhesive film and the copper foil peeled off, but the adhesive was not brittle.

[0236] C: The adhesive was embrittled, but no peeling occurred between the adhesive film and the copper foil.

[0237] D: The adhesive was embrittled, and the adhesive film and the copper foil were peeled off.

[0238] (3% thermal weight loss temperature measurement method)

[0239] The 3% thermal weight loss temperature of the adhesive was measured using TGA Q500 manufactured by TA Instruments. The test conditions were as follows.

[0240] Heating rate: 20℃ / min

[0241] Gas flow rate to the test layer with sample: 20 mL / min

[0242] Sample tray: Platinum

[0243] Example 3 and Comparative Examples 1 to 8

[0244] Test samples of Example 3 and Comparative Examples 1 to 8 were obtained in the same manner as in Example 1 and Example 2 except that the resin film and the adhesive were changed to those shown in Table 2. The obtained test samples were used to perform the same evaluation as in Example 1 and Example 2. The results are shown in Table 2.

[0245] In addition, the resin films and adhesives in Table 2 are as follows.

[0246] (resin film)

[0247] KAPTON EN-S: KAPTON EN-S polyimide film produced by Toray DuPont (thickness 25μm)

[0248] LCP-CTF: LCP Vexter CTF produced by Kuraray Co., Ltd. (thickness 25μm)

[0249] (Adhesive)

[0250] Acrylic rubber (B): Pralux LF manufactured by DuPont (thickness 25 μm), 3% thermal weight loss temperature: 310°C

[0251] Epoxy resin: Epox AH357 (thickness 25 μm) produced by Printec, 3% thermal weight loss temperature: 303°C

[0252]

Claims

1. An adhesive film, wherein an adhesive layer is laminated on a resin film layer, The resin film layer comprises a liquid crystal polymer, The adhesive layer comprises an adhesive, and the adhesive is an acrylic rubber adhesive or an adhesive containing fluororubber. The bonding layer is in the B-grade state. The oxygen permeability of the resin film layer at 200°C measured according to JIS K7126-1 is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less, The 3% thermal weight loss temperature of the adhesive is 320° C. or higher.

2. The adhesive film according to claim 1, wherein The oxygen permeability is 1.00×10 -11 cc cm / cm 2 ·sec·cmHg or less.

3. The adhesive film according to claim 1, wherein The resin film layer further includes a polyimide film.

4. The adhesive film according to claim 2, wherein The resin film layer further includes a polyimide film.

5. The adhesive film according to claim 3, wherein The polyimide film contains polyimide which is a polymer of a tetracarboxylic acid component and a diamine component.

6. The adhesive film according to claim 5, wherein The tetracarboxylic acid component is at least one selected from the group consisting of biphenyltetracarboxylic acid, pyromellitic acid, and their anhydrides and lower alcohol esters, and the diamine component is at least one selected from the group consisting of 1,4-phenylenediamine, 1,3-phenylenediamine, 1,2-phenylenediamine, 2,4-diaminotoluene, 2,5-diaminotoluene and 2,6-diaminotoluene.

7. The adhesive film according to claim 5, wherein The tetracarboxylic acid component is 3,3′,4,4′-biphenyltetracarboxylic dianhydride, and the diamine component is 1,4-phenylenediamine.

8. The adhesive film according to claim 6, wherein The tetracarboxylic acid component is 3,3′,4,4′-biphenyltetracarboxylic dianhydride, and the diamine component is 1,4-phenylenediamine.

9. The adhesive film according to any one of claims 1 to 8, wherein The adhesive includes an acrylic rubber-based adhesive and an adhesive containing fluororubber.

10. The adhesive film according to claim 9, wherein The fluororubber is a polymer or copolymer of at least one monomer selected from the group consisting of ethylene fluoride, vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene.

11. The adhesive film according to claim 10, wherein The fluororubber is a vinylidene fluoride-hexafluoropropylene copolymer.

12. The adhesive film according to claim 9, wherein The fluororubber has an unsaturated bond.

13. The adhesive film according to claim 10 or 11, wherein The fluororubber has an unsaturated bond.

14. A flexible printed substrate, wherein The flexible printed substrate has: a laminated body having at least a first conductor formed with a circuit pattern, a support layer, and a second conductor formed with a circuit pattern in this order; and The adhesive film according to any one of claims 1 to 13, The flexible printed circuit board is formed by contacting the adhesive layer of the adhesive film with both surfaces of the laminate.

15. A flexible printed substrate, wherein The flexible printed substrate has: A laminated body, the laminated body at least having a support layer and a conductor having a circuit pattern formed thereon in sequence; as well as The adhesive film according to any one of claims 1 to 13, The flexible printed circuit board is formed by bringing the surface of the laminate having the conductor into contact with the adhesive layer of the adhesive film. The oxygen permeability of the support layer at 200°C is 1.50×10 -10 cc cm / cm 2 ·sec·cmHg or less.

Citation Information

Patent Citations

  • Metallized polyimide film and method for manufacturing the same

    JP2010023380A

  • Reinforcing film

    CN110003806A

  • Fluoroelastomer curable composition

    WO2019155073A1